SISTEM PENGHANTARAN OBAT MELEWATI BARRIER DARAH OTAK - Syukri, Yandi (Universitas Islam Indonesia, 2004)
ABSTRACTBrain barrier is effective barrier in drug delivery to brain. For effectiveness drug deliveryneed be desaigned a delivery with nanoparticle technology. Nanoparticles are solid colloidalparticles ranging in size from 1 to 1000 nm that are utilized as drug delivery agents. The primaryadvantages of nanoparticle carrier technology is that nanoparticles mask the blood – brain barrierlimiting characteristics of the therapeutic drug molecule. Furthermore, this system may slow drugrelease in the brain, decreasing peripheral toxicity. The method which elaboration in manufacturenanoparticles are emulsion polimerization, interfacial polimerization, desolvation evaporation andsolvent deposition. Currently, report evaluating nanoparticles for brain delivery have studiedanesthetic and chemoterapeutic agent. These studies are reviewed for efficacy and mechanisms oftransport. Physiological factors such as phagocytic activity of the reticuloendothelial system andprotein opsonization may limit the amount of brain delivered drug. Nanoparticle technology appearsto have significant promise in delivering therapeutic molecules across the blood-brain barrier.Key Word : Drug Delivery System, Nanoparticle, Blood-Brain Barrier